EFFECT OF ENVIRONMENTAL PERFORMANCE, COMPANY SIZE, AND PROFITABILITY ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURES - Putri Handayani; Novera Kristianti Maharani (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2021)
Considering how much impact on the environment due to the business activities of mining companies. So companies need to maximize CSR disclosure to gain the trust of stakeholders so that the company can maintain its business life cycle. Therefore, the company needs to establish good relationships with stakeholders. The disclosure of CSR is in this case seen as the method by which existing information about the environmental and social responsibility activities of the organization can develop a good connection to the stakeholders. This study attempts to assess the impact on disclosure of corporate social responsibility by environmental performance, company volume and profitability. The topic of the study is a mining corporation listed between 2014 and 2019 on the Indonesian stock exchange (IDX). In this investigation, collected data was used. In order to collect the samples for this investigation, purposive samples were used. This study uses descriptive statistics to assess the data, whilst the hypotheses can be evaluated via multiple linear regression. Hypotheses show that corporate social responsibility disclosure has little and little impact on the environmental performance and size of the company (CSR). Profitability has a strong beneficial impact on company social responsibility disclosure (CSR). In addition, the disclosure of corporate social responsibility (CSR) is favorably and considerably influenced when environmental performances, firm size and profitability are examined together.